Kontrowersje wokół kulturowego wzorca macierzyństwa w Polsce - Matysiak-Błaszczyk, Agata; Ściupider-Młodkowska, Mirosława (Studia Edukacyjne, 2023)
The article discusses issues related to selected controversies surrounding the cultural pattern of motherhood. In particular, the text analyzes motherhood as a lost value. The core question guiding the considerations relates to the quality of the current dominant construct of the role of the mother, i.e. whether it has a customary/legal/ritual form, or is it currently a rational project consciously chosen by women? The whole discussion was set within a theoretical framework, in what is known as a critical discourse analysis, whose main task was to unmask the myth of motherhood as the only and rightful role, lar- gely dependent on the cultural dominants in a given country.